Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1080/02841859509173412
|View full text |Cite
|
Sign up to set email alerts
|

Colo-Colonic Intussusception Caused by Lipoma

Abstract: Intussusception is primarily seen among children, most often as idiopathic ileocolic intussusception (1, 4), and only 5 to 16% of all intussusceptions are seen in adults (1, 8). In contrast to childhood invagination, in adults underlying pathologic processes are identified in 18 to 90% (1, 8). This report presents 2 cases of colo-colonic intussusception caused by a colonic lipoma. The ultrasonic features of this benign tumour are rather characteristic. A definitive diagnosis can be provided by CT. Case reports

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The pathogenic finding of lipoma upon barium enema is a "squeeze sign," that is, the lipoma changes shape with palpitation, position of patient, and peristalsis (10,12). On CT, lipomas appear ovoid or pear shaped, with sharp margins and with absorption densities of -40 to -120 houns field units, typical of fatty composition (13)(14)(15). Not all intussuscepted lipomas are characterized by homogeneous low attenuation on CT, and a study by Buetow and colleagues (16) showed that they might be mistaken for other neoplastic causes of intussusception such as adenocarcinoma, lymphoma, and metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…The pathogenic finding of lipoma upon barium enema is a "squeeze sign," that is, the lipoma changes shape with palpitation, position of patient, and peristalsis (10,12). On CT, lipomas appear ovoid or pear shaped, with sharp margins and with absorption densities of -40 to -120 houns field units, typical of fatty composition (13)(14)(15). Not all intussuscepted lipomas are characterized by homogeneous low attenuation on CT, and a study by Buetow and colleagues (16) showed that they might be mistaken for other neoplastic causes of intussusception such as adenocarcinoma, lymphoma, and metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…CT scans of colonic lipomas can provide a definite diagnosis because the mass typically has characteristic fatty densitometric values [18,19] . On CT, lipomas appear ovoid or pear shaped, with sharp margins and absorption densities of -40 to -120 Hounsfield units, typical of fatty composition [20,21] . However, these features are evident only in large lesions, as smaller tumors are not detectable due to artifacts and partial volume averaging [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Sonography may also be useful in the diagnosis, particularly in the hands of skilled and experienced operators. 4,5 Because of its low cost, easy applicability, and versatility, it may allow quick assessment of patients, even at the bedside. The applicability of sonography at the bedside increases its importance in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%